Perubahan Ruang Terbuka Publik dan Interaksi Sosial di Kampung Lama (Studi Kasus: Kampung Gandekan dan Kulitan, Semarang) - Inas Nadia Hanifah; Nany Yuliastuti (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Open public space has an important function especially to supporting social interaction. But on the other hand the provision of public open space has its own problems, there is high rate of change of land for settlement because of demands and investments. At the end, it leads to the changes in public open space that makes the changes in social interaction in Kampung Gandekan and Kulitan. This study aimed to assess the changes of open public space and social interaction, as well as to assess the effect of open space changes to the social interaction in Kampung Gandekan and kulitan. The method used in this study is a survey research methods with descriptive and analytical (statistical tests) quantitative approach. Determination of the respondents using the technique of proposive sampling and proportionate stratified random sampling. Based on the analysis within a period of 17 years (1999-2016) showed a change in public open space in Kampung Gandekan and kulitan include; changes in land use as big as 16% of open public space area, changes in the spaces area that more small, change the type and function space as well as the complexity of the condition and utilization spaces. On the same period, social interaction in Kampung Gandekan and Kulitan also decreased regressively into worse condition. It can seen from decreased of average of score social interaction from 18,10 in 1999 become 16,22 in 2016. However, based on the results of research conducted showed no significant effect of public open space changes to change in social interaction. Changes in social interactions that occur are caused by three main factors including age, bustle and characteristic of the original residents as well as migrants.